The magic school bus explores the senses - Cole, Joanna; Degen, Bruce (New York : Scholastic Press, 1999)
Ms. Frizzle and her class explore the senses by traveling on the magic school bus in and out of an eye, ear, mouth, nose, and other parts of both human and animal bodies.
b
b
Keywords: Senses and sensation -- Juvenile literature; Senses and sensation